2022
DOI: 10.1002/csr.2385
|View full text |Cite
|
Sign up to set email alerts
|

Are gender‐diverse boards eco‐innovative? The mediating role of corporate social responsibility strategy

Abstract: Despite the recognized importance of board gender diversity and eco-innovation, it is far from clear how board gender diversity can improve eco-innovation. Grounded in upper echelon theory and the gender socialization theory, we suggest that this relationship operates through corporate social responsibility (CSR) strategy. In a sample of FTSE 350 firms, we find that CSR strategy mediates the influence of the board's gender diversity on eco-innovation. These findings are robust to several regression specificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 78 publications
2
25
0
Order By: Relevance
“…The interest variable in this study is board gender diversity (BGD), which is defined as the percentage of women on the board of directors. The use of this measure is consistent with previous studies on board diversity, such as Bear et al (2010), Francoeur et al (2019) and Issa and Bensalem (2022). Using a consistent measure across studies allows for comparison of results and contributes to the body of knowledge on the topic.…”
Section: Reducing Esg Controversiessupporting
confidence: 69%
See 1 more Smart Citation
“…The interest variable in this study is board gender diversity (BGD), which is defined as the percentage of women on the board of directors. The use of this measure is consistent with previous studies on board diversity, such as Bear et al (2010), Francoeur et al (2019) and Issa and Bensalem (2022). Using a consistent measure across studies allows for comparison of results and contributes to the body of knowledge on the topic.…”
Section: Reducing Esg Controversiessupporting
confidence: 69%
“…Research has shown that the composition of a company’s board of directors can have an impact on corporate decisions related to ESG issues and can help to reduce controversies related to these matters (Issa and Fang, 2019). For instance, board gender diversity is found to be linked to improved waste management and recycling (Gull et al , 2023), reduced biodiversity impact (Haque and Jones, 2020), decreased environmental emissions (Kyaw et al , 2022) and enhanced eco-innovation (Issa and Bensalem, 2022). Board gender diversity is also associated with improved accounting misreporting (Wahid, 2019), earnings quality (Srinidhi et al , 2011) and accounting misreporting (Cumming et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Our study focuses on the variable of BGD, which is defined as the percentage of women serving on a company's board of directors. This measure is widely used in previous research on board diversity and allows for comparability with other studies in the field (Bear et al, 2010; Francoeur et al, 2019; Issa & Bensalem, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The presence of female directors on corporate boards is widely recognized as a critical aspect of effective corporate governance. Female directors can bring valuable contributions to boardroom discussions, positively impacting the decision‐making process and promoting biodiversity conservation (Haque & Jones, 2020; Issa & Bensalem, 2022; Zaid et al, 2020). Furthermore, having female directors on corporate boards can positively impact environmental sustainability, according to resource dependency theory and upper echelon theory.…”
Section: Introductionmentioning
confidence: 99%
“…In today’s business landscape, companies are expected to operate responsibly, making environmental sustainability an important factor in their overall strategy (Issa and Bensalem, 2022). Companies must recognize the multiple stakeholders they impact, including the environment, and understand that their actions towards environmental protection can have a significant impact on their financial performance.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%